Musical Aspects for Empowering the Black Characters in the Movie Get Out (2017) - Syeikha Annisa Marasabessy; Lucia Lusi Ani Handayani (Institut Seni Indonesia Yogyakarta, 2019)
In this 21st century, the representation of Black people in many U.S. movies is still problematic, for the movies do not omit the stereotypical representations of Black people, which are often depicted being disrespectful and unintelligent compared to other races. Many movies have been trying to change them into another perspective, yet they are still unable to completely get rid of those stereotypes. By looking through the cinematic aspects, the dialogues, and the symbols along with the sounds and music used, this paper examines the stereotypes of Black characters the movie Get Out (2017) by Jordan Peele using discourse analysis. The paper observes that the representation of the movie still distinguishes Black from White in the aspects of body over mind in Black masculinity, incivility, and distinctive racial labor. As a result, Black characters are seen inferior compared to White characters despite the movie’s effort to empower them. The use of music also emphasizes the power relation difference between the two races. Overall finding of the paper reveals that the existence of Black stereotypical depiction is still found in a movie empowering Black people showing that race representation should be monitored thoroughly.